Representations of DIY Culture in Youth Groups: a Case Study of Punk Subculture in Lithuania - Šatūnienė, Reda (Sociologija. Mintis ir veiksmas, 2011)
The main object of this paper is to present representations of DIY culture in Lithuanian non-commercial punk subculture. Ethnographic qualitative research methods were used to obtain empirical data, including interviews, questionnaires, analysis of group documents, audio and video recordings, etc, along with Clifford Geertz’s interpretative anthropological methods. The data was gathered between 2005-2008. During the research, 30 semi-structured in-depth interviews were undertaken. The analysis shows that anti-consumer values in Lithuanian subculture are closely connected with DIY culture. The appreciation of these attitudes derives from protest against ‘the system’, avoidance of the official bureaucratic apparatus and the belief among participants that everything that is done officially can be achieved equally well by themselves. The organisation of concerts, the making of fanzines and other events on the punk scene are based on the enthusiasm and voluntarism the those involved. Subcultural activity enables its members’ self-confidence, and constructs an active, conscious and critical self-image.